Storage management and wastage of reproductive health medicines and associated challenges in west Wollega zone of Ethiopia: a mixed cross-sectional descriptive study - Oliyad Kebede; Gizachew Tilahun; Desalegn Feyissa (BMC, 2021)
Abstract Background Keeping proper storage conditions at health facilities is vital to reduce pharmaceutical wastage caused by environmental factors. The expiration of medicines at the health facilities could lead to wastage of potentially life-saving drugs and unnecessary expenditure on the disposal of those expired medicines. Therefore, the aim of this study was to assess pharmaceutical stores and wastage of reproductive health medicines due to expiration in the west Wollega zone of Ethiopia. Method We conducted a facility-based cross-sectional study from 15th to 31st July 2019 using quantitative and qualitative data from West Wollega Zone of Ethiopia. Results Among 23 health facilities assessed, 17 (73.91%) (4(100%) hospitals and 13(68.42%) health centers) fulfilled desirable storage conditions. Hospitals' stores had equipment and furniture, fulfilled desirable storage conditions, whereas, a significant number of the health centers' stores did not comply with desirable storage conditions. Challenges of store management identified were poor store infrastructure and shortage of manpower. The total value of reproductive health medicines wasted due to expire in surveyed facilities was 357,920.52 ETB (12,323.81 US dollars) and the Percentage of Stock Wasted due to Expiration was 8.04%. Levonorgestrel 0.75 mg tablet is the highest in the percentage of stock wasted due to expiry. Factors contributing to wastage due to expiration were supply and demand imbalance. Conclusion Reproductive health medicines wasted due to expiration is high compared to the government of Ethiopia's plan for the year 2018/19. This might imply that the monitoring of this plan is poor. Even though hospitals store management is good, there is a weakness in store management in health centers. This could be due to poor attention given to health centers. Therefore, west Wollega zonal health department should appropriately monitor the wastage of Reproductive health medicines and enforce health centers to follow appropriate storage guidelines. Hospitals and health centers should not accept medicines beyond their need to reduce expiry.